The Negative Impact Of Consuming Traditional Medicine Made From Natural Herbs (Jamu) On The Knowledge Of Pregnant Women - Rahmat Pannyiwi; Rezqiqah Aulia Rahmat; Rifqi Ferry Balfas (International Journal of Health Sciences, 2026)
Background: Traditional herbal medicines, including herbal remedies, are widely used in the community and can also be consumed by pregnant women. Limited knowledge regarding these aspects may increase the risk of inappropriate herbal use during pregnancy. Objective: This study aims to determine the impact of traditional herbal medicine consumption on pregnant women's knowledge regarding the safety and potential negative effects of herbal medicine use during pregnancy. Method: This study used a quantitative descriptive analytical design with a cross-sectional approach. This study involved 80 pregnant women selected using purposive sampling. Data were collected using a structured questionnaire that assessed knowledge about herbal medicine safety, consumption behavior, reasons for consumption, and potential risks during pregnancy. Data were analyzed using frequency distribution and cross-tabulation, with the Chi-Square test used to examine the relationship between knowledge level and herbal medicine consumption. Results: The results showed that 46 respondents (57.5%) had good knowledge and 34 respondents (42.5%) had poor knowledge. A total of 31 respondents (38.8%) reported consuming traditional herbal medicine during pregnancy. Among respondents with poor knowledge, 20 (58.8%) consumed herbal medicines, compared to 11 (23.9%) among respondents with good knowledge. Statistical analysis showed a significant association between knowledge level and herbal medicine consumption (p=0.003). Conclusion: Herbal medicine consumption during pregnancy was more common among respondents with inadequate knowledge. Improving the knowledge of pregnant women through appropriate health education and consultation with health professionals is important to minimize the inappropriate use of traditional herbal medicines during pregnancy.